2023
DOI: 10.32471/exp-oncology.2312-8852.vol-42-no-1.14147
|View full text |Cite
|
Sign up to set email alerts
|

Survival analysis of oropharyngeal squamous cell carcinoma patients linked to histopathology, disease stage, tumor stage, risk factors, and received therapy

Abstract: Summary. Background: Survival of oropharyngeal squamous cell carcinoma (OSCC) patients depends on the risk and environmental factors, tumor biology, achievements in diagnostics and treatment approaches. Aim: To perform a survival analysis of the patients with OSCC treated over a 10-year period in a single hospital in Latvia linking these data to histopathological findings, risk factors and received therapy. Materials and Methods: The main outcome measures were overall and disease-specific survival (OS and DS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
1
0
1
Order By: Relevance
“…Cox regression analysis indicated that advanced clinical stages were associated with poorer survival in OSCC patients. This result is compatible with other studies showing that patients with OSCC are commonly diagnosed late, a fact that negatively influences their prognosis ( 16 , 25 ). This late diagnosis has been attributed to factors such as the absence of initial symptoms, the patient’s lack of knowledge about the disease, and the fear of diagnosis.…”
Section: Discussionsupporting
confidence: 93%
“…Cox regression analysis indicated that advanced clinical stages were associated with poorer survival in OSCC patients. This result is compatible with other studies showing that patients with OSCC are commonly diagnosed late, a fact that negatively influences their prognosis ( 16 , 25 ). This late diagnosis has been attributed to factors such as the absence of initial symptoms, the patient’s lack of knowledge about the disease, and the fear of diagnosis.…”
Section: Discussionsupporting
confidence: 93%
“…This difference may be explained by different lifestyles, preferences, and sexual habits. Notably, smoking, recognized as a significant factor influencing the development of head and neck cancer, is a common hazard in Latvian society [52]. However, the present study suggests a role of HPV in the carcinogenesis of non-oropharyngeal cancer and points at HPV16 being a predominant HPV type confirmed in LSCC and HPSCC.…”
Section: Discussioncontrasting
confidence: 51%